Microgravity inhibits decidualization via decreasing Akt activity and FOXO3a expression in human endometrial stromal cells - Hye-Jeong Cho (Nature Portfolio, 2019)
Abstract Decidualization is characterized by the differentiation of endometrial stromal cells (eSCs), which is critical for embryo implantation and maintenance of pregnancy. In the present study, we investigated the possible effect of simulated microgravity (SM) on the process of proliferation and in vitro decidualization using primary human eSCs. Exposure to SM for 36 h decreased the proliferation and migration of eSCs significantly, without inducing cell death and changes in cell cycle progression. The phosphorylation of Akt decreased under SM conditions in human eSCs, accompanied by a simultaneous decrease in the level of matrix metalloproteinase (MMP)-2 and FOXO3a. Treatment with Akti, an Akt inhibitor, decreased MMP-2 expression, but not FOXO3a expression. The decreased level of FOXO3a under SM conditions impeded autophagic flux by reducing the levels of autophagy-related genes. In addition, pre-exposure of eSCs to SM significantly inhibited 8-Br-cAMP induced decidualization, whereas restoration of the growth status under SM conditions by removing 8-Br-cAMP remained unchanged. Treatment of human eSCs with SC-79, an Akt activator, restored the reduced migration of eSCs and decidualization under SM conditions. In conclusion, exposure to SM inhibited decidualization in eSCs by decreasing proliferation and migration through Akt/MMP and FOXO3a/autophagic flux.